2021
DOI: 10.3390/biology10040270
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size Covaries More Positively with Propagule Size than Adult Size: New Insights into an Old Problem

Abstract: The body size and (or) complexity of organisms is not uniformly related to the amount of genetic material (DNA) contained in each of their cell nuclei (‘genome size’). This surprising mismatch between the physical structure of organisms and their underlying genetic information appears to relate to variable accumulation of repetitive DNA sequences, but why this variation has evolved is little understood. Here, I show that genome size correlates more positively with egg size than adult size in crustaceans. I exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 595 publications
(526 reference statements)
1
24
0
Order By: Relevance
“…As expected from predictions of cell SA theory, multiple studies have reported negative associations between R / M and cell size (or its proxy, genome size) among related animal species, including carabid beetles [ 41 ], amphibians [ 22 , 28 , 54 ], eyelid geckos [ 32 ], birds [ 28 , 40 , 55 ], and mammals [ 26 ] (for recent reviews, see [ 20 , 56 , 57 ]). Most of these studies have focused on the sizes of erythrocytes (red blood cells), which are importantly involved in oxygen exchange in respiratory systems and thus may be linked to R / M for this reason.…”
Section: Major Ways That Variation In Metabolic Rate May Relate To Ce...mentioning
confidence: 94%
“…As expected from predictions of cell SA theory, multiple studies have reported negative associations between R / M and cell size (or its proxy, genome size) among related animal species, including carabid beetles [ 41 ], amphibians [ 22 , 28 , 54 ], eyelid geckos [ 32 ], birds [ 28 , 40 , 55 ], and mammals [ 26 ] (for recent reviews, see [ 20 , 56 , 57 ]). Most of these studies have focused on the sizes of erythrocytes (red blood cells), which are importantly involved in oxygen exchange in respiratory systems and thus may be linked to R / M for this reason.…”
Section: Major Ways That Variation In Metabolic Rate May Relate To Ce...mentioning
confidence: 94%
“…This negative correlation has been demonstrated in some diploid plants and some insects, crustaceans, salamanders, and mammals (Bennett, 1987 ; White and Mclaren, 2000 ; Gregory, 2002b , 2005a ; Alfsnes et al, 2017 ). In addition, in many animals, metabolic rate (Kozłowski et al, 2003 ; Gardner et al, 2020 ), body size (Glazier, 2021 ), chromosome number (Ardila-Garcia and Gregory, 2009 ), and latitude (Carta and Peruzzi, 2016 ) and altitude (Reeves et al, 1998 ; Akbudak et al, 2018 ) also exhibit well-established correlations with genome size. Although these organism level correlations are not universal across all taxonomic groups, all taxonomic groups at least exhibit correlations between genome size, cell size, and cell division rate.…”
Section: Introductionmentioning
confidence: 99%
“…Genome size is one of the most fundamental biological traits of living organisms, not only containing genetic information (genotypic) but also providing an organism's structural components (nucleotypic) (Glazier, 2021 ; Johnson et al, 2021 ). At the same time, genome size represents an important basis for comparative research into genome evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we were not able to confirm the previously formulated indication of a positive genome and body size relationship [ 29 ]. Nevertheless, other morphological traits might be interesting to study in this context as e.g., genome size in crustaceans was shown to relate more to the size of propagules rather than to adult body size [ 73 ].…”
Section: Discussionmentioning
confidence: 99%